Theology and cosmology in Plato - Escobar Moncada, Jairo Iván (Estudios de Filosofía, 1996)
It is stated that the base of cosmological logos is the theology established in Plato 's Timaeus: So, the purpose of the mythic discourse pervading the whole dialogue is to draw the predominance of reason, beauty and arder (kosmos) in relation to chance and necessity in the world. This thesis is supported on a philosophical analysis of the role of divine Demiurgos in contrast to that of Christian and Greek gods. In the first case, it is not a question of exnihilo creation but of an ordering of pre-existent material. In the second case, there is not an anthropomorphic god but a "philanthropic" one, on whom it falls the responsibility of the existence of a cognoscible kosmos, model of human praxis.